Technology Integrated Formative Assessment: Effects on Students’ Conceptual Knowledge and Motivation in Chemical Equilibrium - Tadesse Hagos; Dereje Andargie (JCER (Journal of Chemistry Education Research), 2022)
The main objective of this study was to evaluate the impact of technology integrated formative assessment strategies on students’ conceptual knowledge and their motivation in chemical equilibrium. Quasi-experimental control group interrupted time series design was employed. Data were collected from 132 students which were selected using multistage random sampling technique from three governmental secondary schools. Two experimental (Technology Integrated Formative Assessment (TIFA) and Formative Assessment (FA) alone) and one comparison groups were involved in the study. A series of chemical equilibrium conceptual tests and motivation questionnaire were used to collect data. One-way ANOVA and Mixed model ANOVA were used to analyze the test scores. There was a statistically significant difference between groups in posttest on conceptual plus remembering (F (2,129) = 3.52, p=.033), understanding (F (2,129) = 4.70, p=.033), applying (F (2, 129) = 20.35, p<.001) and their motivation (F (2, 129) = 12.375, p< .001). However, there were no statistically significant differences among groups in posttest on conceptual plus analysis (F (2, 129) = 1.10, p = .335) and evaluating (F (2,129) = 3.03, p = .052). There was also an interaction effect between treatment and time point on the conceptual test scores. It was concluded that TIFA more effective in facilitating students’ conceptual knowledge and motivation in learning chemical equilibrium than the two other groups. The researchers recommended that chemistry teachers should adapt TIFA as a teaching strategy in chemistry classrooms and laboratories. They are also recommended that teachers should incorporate it into their classes to enhance students’ motivation. Key Words: Conceptual knowledge, Formative assessment, Motivation, Technology